Evaluation, diagnosis and psychological treatment in a case of body dysmorphic disorder - Santos Morocho, José Luis (2019)
Introduction: Body Dysmorphic Disorder (BDD) is a disabling mental condition that generates concern for body image. The objective was to describe the evaluation, diagnosis and treatment of a case of BDD. Materials and methods: observational, descriptive, clinical case study. The evaluation instruments were: the questionnaire Dysmorphic Concern Questionnaire, Body Dysmorphic, the Disorder Modification, and the Goldberg General Health Questionnaire; applied during the second week (test), sixth week (retest) and ninth week (follow-up). For the diagnosis, the Body Dysmorphic interview, expert judgment and structured interviews were used. For the treatment, a model of psychological mediation, cognitive behavioral therapy was included Expert judgment and structured interviews. The treatment included a model of psychological mediation and a model of cognitive behavioral therapy, with training techniques in relaxation, in vivo exposure and cognitive restructuring. The charts and tables were made with the free program of excel 2010. Results: Cognitive and behavioral strategies were included. The patient learned to test his beliefs about body image, through social experiments, modified his worries and behaviors towards himself, decreased his anxiety and embarrassment. Discussion: a significant reduction in repetitive behavior was found (bronzing-mirroring). The limitation was not to include more techniques.